Association of DNA methylation status, gene and protein expression of her family in colorectal adenocarcinoma - Othman @ Jaffar, Rosfayati (2020)
Colorectal cancer (CRC) is the third most common cancer worldwide and the second leading cancer in Malaysia. Despite advanced therapies, many cases of recurrence and resistance have been reported. Surgery is only applicable for early diagnosed CRC cases. Reliable biomarkers are very crucial for early diagnosis, prognosis and therapeutic target. Overexpression of HER family members (EGFR, HER2, HER3 and HER4) has been associated with oncogenic transformation via DNA methylation of the promoter regions. Aberrant DNA methylation of HER family members has been implicated in carcinogenesis of CRC mainly through the regulation of gene expression. This study aimed to determine the DNA methylation status and gene expression of HER family members in CRC cell lines and in formalin-fixed paraffin embedded (FFPE) samples as well as the protein expression of HER family members in FFPE samples. The associations of DNA methylation status, gene and protein expression of these genes in FFPE samples were also determined. Fifty-nine archival FFPE CRC cases with the adjacent normal colon tissues were retrieved. The selected tissues were micro-dissected manually prior to RNA and DNA extraction. Gene expression and DNA methylation status of HER family members were evaluated by qPCR and MSP technique respectively. Protein expression was determined using immunohistochemistry (IHC) technique. Prior to FFPE, the same procedures were performed on CRC cell lines i.e. HT-29, HCT116, Caco-2 and CCD 841 CoN (normal colon) with treatment of 5’-aza-2’-deoxytidine (5-aza-dC) and 5-fluorouracil (5-FU). Upregulation of HER family members were discovered in all CRC cell lines with HER3 recorded significant expression (p<0.0001). EGFR and HER3 were hypomethylated whereas HER4 was hypermethylated in CRC cells. Downregulation of all genes were observed in several CRC cell lines after treatment with only HER3 shows significant result (p<0.001). EGFR, HER2 and HER3 remained unmethylated after being treated with 5-FU and HER4 was unmethylated after treatment with 5-aza-dC. Overexpression of EGFR (54.2%, p-value=0.021), HER2 (52.5%, p-value=0.022), and HER3 (42.4%, p-value=0.077) and hypomethylation of EGFR (81.4%) and HER3 (91.5%) were discovered in FFPE CRC tissues. Positive proteins expressions of EGFR (42.4%), HER2 (11.9%), HER3 (47.5%) and HER4 (57.6%) were seen in FFPE tissues. However, no significant association was found between DNA methylation, mRNA levels and protein expression of HER family members. Aberrant DNA methylation pattern of HER3 showed significant association with tumour differentiation (p-value=0.035) and tumour location (p-value=0.007). Even though our data suggest that there is no significant relationship between DNA methylation and mRNA expression, the aberrant regulation and hypomethylation of these genes strongly suggest the important role of these genes in tumourigenesis of CRC. Hypomethylation facilitates the activation of these genes which promotes oncogenic cell growth, loss of imprinting or genomic instability and subsequently promotes carcinogenesis and progression of CRC. Therefore, HER family has a potential as prognostic factors and therapeutic target for CRC. The genes are very promising candidates for the identification of new biomarkers. However, further investigation on DNA hypomethylation is required.